Thyroid hormone signalling genes are regulated by photoperiod in the hypothalamus of F344 rats. - Alexander W Ross; Gisela Helfer; Laura Russell; Veerle M Darras; Peter J Morgan (PLoS ONE)
Seasonal animals adapt their physiology and behaviour in anticipation of climate change to optimise survival of their offspring. Intra-hypothalamic thyroid hormone signalling plays an important role in seasonal responses in mammals and birds. In the F344 rat, photoperiod stimulates profound changes in food intake, body weight and reproductive status. Previous investigations of the F344 rat have suggested a role for thyroid hormone metabolism, but have only considered Dio2 expression, which was elevated in long day photoperiods. Microarray analysis was used to identify time-dependent changes in photoperiod responsive genes, which may underlie the photoperiod-dependent phenotypes of the juvenile F344 rat. The most significant changes are those related to thyroid hormone metabolism and transport. Using photoperiod manipulations and melatonin injections into long day photoperiod (LD) rats to mimic short day (SD), we show photoinduction and photosuppression gene expression profiles and melatonin responsiveness of genes by in situ hybridization; TSHβ, CGA, Dio2 and Oatp1c1 genes were all elevated in LD whilst in SD, Dio3 and MCT-8 mRNA were increased. NPY was elevated in SD whilst GALP increased in LD. The photoinduction and photosuppression profiles for GALP were compared to that of GHRH with GALP expression following GHRH temporally. We also reveal gene sets involved in photoperiodic responses, including retinoic acid and Wnt/ß-catenin signalling. This study extends our knowledge of hypothalamic regulation by photoperiod, by revealing large temporal changes in expression of thyroid hormone signalling genes following photoperiod switch. Surprisingly, large changes in hypothalamic thyroid hormone levels or TRH expression were not detected. Expression of NPY and GALP, two genes known to regulate GHRH, were also changed by photoperiod. Whether these genes could provide links between thyroid hormone signalling and the regulation of the growth axis remains to be investigated.